Pengaruh Arus Kas Operasi, Profitabilitas, Likuiditas, dan Solvabilitas Terhadap Financial Distress - Fitriani, Emilia; Ulupui, I Gusti Ketut Agung; Respati, Dwi Kismayanti (LPPM Universitas Negeri Jakarta, 2023)
The Effect of Operating Cash Flow, Profitability, Liquidity, and Solvency on Financial Distress in Transportation and Logistics Sector Companies Listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. This research was conducted to determine the effect of operating cash flow, profitability, liquidity and solvency on financial distress. This research uses transportation and logistics sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period as the population. This research method uses quantitative methods with data in the form of financial reports available IDX website. The sample was selected using purposive sampling and produced 76 observation data. The data were processed using the SPSS application and analyzed using logistic regression analysis. Based on the results of the analysis conducted, it can be concluded that operating cash flow and liquidity does not have a significant effect on financial distress. Meanwhile, profitability have a negative and significant effect on financial distress and solvency has a positive and significant effect on financial distress.